The salt crystal structure of etoricoxib hydrochloride, C18H16Cl2N2O2S - Ma Yu-Heng; Hong Wei-Pu; Qian Yan-Ling; Tao Zhen-Wei; Hou Shi-Qi; Guo Jia-Le; Ma Wen-Jing; Wang Yi-Hong (Zeitschrift für Kristallographie - New Crystal Structures)
C18H16Cl2N2O2S, monoclinic, P21/c (no. 14), a = 10.915(2) Å, b = 11.801(2) Å, c = 14.059(3) Å, β = 90.10(3)°, V = 1810.9(6) Å3, Z = 4, R gt(F) = 0.0585, wR ref(F 2) = 0.1532, T = 293(2) K.